ANALYSIS OF FORMALIN CONTENT IN SOME FRESH FISH IN PARLUASAN TRADITIONAL MARKETS PEMATANGSIANTAR CITY - Simanjuntak, Hendra; Silalahi, Mastiur Verawaty (JST (Jurnal Sains dan Teknologi), 2022)
Fish is considered a key nutrient for a balanced diet for the growing population Â around the world..fish is also superior because it is the highest natural source of omega 3 fatty acids. These fishery products are susceptible to quality degradation, therefore many use formalin as a fish preservative. The purpose of this study was to determine the level of formalin in some fresh fish. The method used is a quantitative test of formalin levels with a formalin test kit and descriptively. The sample used 5 types of fresh fish from 10 respondents. And the results of this study were that the five fresh fish samples contained formalin because the five fish were â€œone the fishingâ€ fish. The most formalin content found in snapper was 3.42 g/ml.